Implementasi Modul Invers Matriks dalam Menyelesaikan Soal Katrol Tetap untuk Meningkatkan Hasil Belajar Siswa - Dina Mahartika (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Teaching materials in the form of pulley learning modules are still rarely used in high school, and the methods commonly applied are conventional such as substitution and elimination, which have long and multilevel stages. This makes fixed pulley one of the physics materials that are difficult to understand. This study aims to improve student learning outcomes through the use of matrix inverse modules in solving fixed pulley problems. The method used is an experiment with a quantitative descriptive approach and a One Group Pretest Posttest Design research design. Data were collected through learning outcome tests consisting of pretest and posttest, and data analysis was conducted using the N-Gain test. The results showed that the application of the fixed pulley problem solving module with the inverse matrix method succeeded in improving students' physics learning outcomes, as evidenced by the N-Gain value of 0.71, which is included in the high category. The interview results showed harmony with the data analysis of student learning outcomes. Students also gave a positive response to the use of the inverse matrix method although there were still some students who still experienced problems such as in the review of objects and determining the adjoin. Thus, the use of the inverse matrix learning module on pulley material can still have a positive impact on improving student learning outcomes, making it an effective alternative to overcome difficulties in understanding the physics material.
Reaploud Repository February_Hasyim
Keywords: Learning Outcomes; Matrix Inverse; Learning Module; Fixed Pulley